Spatial and Temporal Variation Characteristics of Air Pollutants in Coastal Areas of China: From Satellite Perspective - Xinrong Yan; Juanle Wang; Fang Wu; Jing Bai; Xun Zhang; Guiping Li; Haibo Fei (Remote Sensing)
Under increasingly stringent global policies aimed at reducing emissions from shipping, the impact of maritime activities on air quality has garnered significant attention. However, the absence of comprehensive macro-evaluation methods and a limited understanding of regional-scale pollutant emissions introduce substantial uncertainties in assessing emission reduction effectiveness and identifying pollution sources. In this study, we utilized Sentinel-5P satellite data from 2019 to 2024 to examine the spatiotemporal characteristics of six air pollutants (SO2, NO2, HCHO, O3, CO, and CH4) in China’s coastal areas. We further investigated the correlation between ship density and pollutant concentrations and analyzed the distribution of pollutant concentrations in major coastal ports across China. The results indicate the following: (1) The concentrations of SO2, HCHO, and CH4 exhibited a continuous increasing trend, whereas NO2, CO, and O3 remained relatively stable or showed a slight decline. All six pollutants demonstrated obvious seasonal variations, with NO2 and HCHO following a double-peak pattern and O3, SO2, CH4, and CO exhibiting a single-peak pattern. (2) Pollutant concentrations were higher along the northern coast (Yellow Sea and Bohai Sea) and relatively lower in the South China Sea region. Specifically, NO2, SO2, and O3 were higher in the Bohai Sea region; HCHO and CO were more concentrated in the northern coastal area; and CH4 was elevated in the north and certain ports of the Yangtze River Delta. (3) Ship density displayed a significant positive correlation with NO2, SO2, HCHO, CO, and CH4, indicating that ship emissions are an important source of these pollutants. Although O3 is not directly emitted by ships, a positive correlation was observed in certain ship-dense areas, primarily due to photochemical reactions involving NO2 and volatile organic compounds (VOCs). (4) Higher concentrations of NO2, SO2, HCHO, CO, and CH4 were observed in northern ports (e.g., Tianjin Xingang, Qinhuangdao, Tangshan, and Dalian), whereas southern Chinese ports (e.g., Shenzhen, Xiamen, and Haikou) exhibited lower pollution levels. These findings provide a scientific foundation for coastal air pollution control and highlight the necessity of ship emission regulation and integrated multi-pollutant management.